2016
DOI: 10.1002/jmv.24603
|View full text |Cite
|
Sign up to set email alerts
|

Alternate circulation and genetic variation of human respiratory syncytial virus genotypes in Chengdu, West China, 2009‐2014

Abstract: Human respiratory syncytial virus (HRSV) is a major pathogen that causes worldwide seasonal epidemic disease in infants due to its genetic variations. However, published information on the molecular epidemiology of HRSV was never reported particularly in Chengdu of West China. During five consecutive seasons (from 2009 to 2014), 433 (23.7%) of 1827 samples from hospitalized patients were identified as HRSV positive. Epidemiological characteristics of HRSV revealed that subtype A viruses (62.7%) prevailed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
(73 reference statements)
3
14
0
2
Order By: Relevance
“…To better understand the epidemiological characteristics of RSV subtypes, RSV-A and RSV-B subtypes were determined based on 623 RSV-positive samples from 13 hospitals. The results showed that RSV-A was the dominant subtype circulating in Guangzhou during 2011-2016, consistent with reports from other regions (Hu et al, 2017;Slovic et al, 2016). The three patients with co-detection were all infants and toddlers and inpatients with ALRI, and none of them died.…”
Section: Discussionsupporting
confidence: 87%
“…To better understand the epidemiological characteristics of RSV subtypes, RSV-A and RSV-B subtypes were determined based on 623 RSV-positive samples from 13 hospitals. The results showed that RSV-A was the dominant subtype circulating in Guangzhou during 2011-2016, consistent with reports from other regions (Hu et al, 2017;Slovic et al, 2016). The three patients with co-detection were all infants and toddlers and inpatients with ALRI, and none of them died.…”
Section: Discussionsupporting
confidence: 87%
“…Considering HCMV reactivation/reinfection, seasonality has rarely been discussed . Due to weather conditions from winter to spring and prevalent features of certain viruses , the proportion of detected HCMV infections may rise with the growth of the incidence of RI, regardless of primary or secondary infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several genotypes have been described in subgroups A (GA1 to GA7, SAA1 and NA1, NA2) and B (URU1, URU2, and GB1 to GB4, SAB1 to SAB3, and BA1 to BA13). The recently described genotype HRSV A ON1 is characterized by the duplication of 72 nucleotides in gene G. After being reported in Canada, HRSVA ON1 has also been identified in Europe, India, Africa, South America, and Asia [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%